Dietary intake and food sources of choline in European populations. Issue 12 (1st October 2015) - Vennemann, Francy B. C.; Ioannidou, Sofia; Valsta, Liisa M.; Dumas, Céline; Ocké, Marga C.; Mensink, Gert B. M.; Lindtner, Oliver; Virtanen, Suvi M.; Tlustos, Christina; D'Addezio, Laura; Mattison, Irene; Dubuisson, Carine; et al.
Abstract: Choline is an important nutrient for humans. Choline intake of the European population was assessed considering the European Food Safety Authority European Comprehensive Food Consumption Database and the United States Department of Agriculture Nutrient Database. Average choline intake ranges were 151–210 mg/d among toddlers (1 to ≤3 years old), 177–304 mg/d among other children (3 to ≤10 years old), 244–373 mg/d among adolescents (10 to ≤18 years old), 291–468 mg/d among adults (18 to ≤65 years old), 284–450 mg/d among elderly people (65 to ≤75 years old) and 269–444 mg/d among very elderly people (≥75 years old). The intakes were higher among males compared with females, mainly due to larger quantities of food consumed per day. In most of the population groups considered, the average choline intake was below the adequate intake (AI) set by the Institute of Medicine in the USA. The main food groups contributing to choline intake were meat, milk, grain, egg and their derived products, composite dishes and fish. The main limitations of this study are related to the absence of choline composition data of foods consumed by the European population and the subsequent assumption made to assess their intake levels. Given the definition of AI, no conclusion on the adequacy of choline intake can be drawn for most European population groups. Such results improve the knowledge on choline intake in Europe that could be further refined by the collection of choline composition data for foods as consumed in Europe.